2020
DOI: 10.1101/2020.07.01.182550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early postmortem mapping of SARS-CoV-2 RNA in patients with COVID-19 and correlation to tissue damage

Abstract: AbstractClinical observations indicate that COVID-19 is a systemic disease. An investigation of the viral distribution within the human body in correlation to tissue damage can help understanding the pathophysiology of SARS-CoV-2 infection.We present a detailed mapping of viral RNA in 61 tissues and organs of 11 deceased patients with the diagnosis COVID-19. The autopsies were performed within the (very) early postmortem interval (mean: 5.6 hours) to avoid bias… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 46 publications
4
46
0
1
Order By: Relevance
“…Taken together, these results indicate that endothelial cells of the lung model are not the primary target cells of SARS-CoV-2 which is in agreement with previous studies (Bar-On et al, 2020). Further, it is in line with the observation that endothelial layer of the alveolar capillaries of deceased COVID-19 patients were still intact but epithelial tissue was found seriously damaged (Deinhardt-Emmer et al, 2020b). Although the mechanism is not clear the increased proinflammatory cytokine release might cause an endothelial dysfunction.…”
Section: Sars-cov-2 Infects Epithelial Cells Within the Alveolus-on-asupporting
confidence: 85%
See 1 more Smart Citation
“…Taken together, these results indicate that endothelial cells of the lung model are not the primary target cells of SARS-CoV-2 which is in agreement with previous studies (Bar-On et al, 2020). Further, it is in line with the observation that endothelial layer of the alveolar capillaries of deceased COVID-19 patients were still intact but epithelial tissue was found seriously damaged (Deinhardt-Emmer et al, 2020b). Although the mechanism is not clear the increased proinflammatory cytokine release might cause an endothelial dysfunction.…”
Section: Sars-cov-2 Infects Epithelial Cells Within the Alveolus-on-asupporting
confidence: 85%
“…Clinical studies revealed that the virus primarily replicates in the lung, which can cause severe lung damage up to necrotic destruction of large areas of the lung tissue (Carsana et al, 2020). In autopsies of deceased COVID-19 patients, it has been observed that particularly in severe cases viral particles can disseminate throughout the body (Deinhardt-Emmer et al, 2020b;Wichmann et al, 2020). Additionally, systemic complications have been reported, such as the massive release of proinflammatory cytokines and thromboembolic events in various organs (Becker, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even though SARS‐CoV‐2 is also detectable in the bone marrow, it has not been demonstrated whether haemophagocytosis in COVID‐19 patients is caused by direct viral infection of phagocytes or indirectly by a systemic immune response 2 . To elucidate this, histological bone marrow analysis and additional SARS‐CoV‐2 RNA determination in these bone marrow samples would be required.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology and mechanisms of the immune response in COVID‐19 patients have not yet been completely elucidated. Although respiratory symptoms such as dyspnoea or cough are predominant, the virus affects the entire host organism, and has been detected in many organs by the use of molecular techniques 1,2 . Especially in patients with severe COVID‐19, dysregulation of the immune system, with elevated levels of proinflammatory cytokines, increased numbers of neutrophils, and decreased numbers of lymphocytes, has been reported 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, neutrophil alterations observed in our recovered cohort were induced after the successful displacement of the virus by the immune system. This might be indicative for SARS-CoV-2 causing long-term immunological signals or even targeting bone marrow stem cells, as viral RNA was found post-mortem in patient bone marrow (53).…”
Section: Discussionmentioning
confidence: 99%